Radio frequency spectrum, the out of sight, out of mind national strategic resource - Zimri, Peter John (My University, 2014)
Radio frequency spectrum, a scarce national strategic asset, has not enjoyed the necessary attention and protection it deserves. Spectrum has been managed by the same approach over the last two decades and it is only recently that attention has been given to it due to the pressure of increased competition and technological advancements. The purpose of this study was to explore the policy and regulatory approaches to the management of radio frequency spectrum prevalent in South Africa today. Internationally there is a shift from the traditional command and control spectrum management approaches to more market-based mechanisms, such as auctions and spectrum trading. The South African approach has been marked by delays in the usage of spectrum as a result of the current institutional arrangements where there is an apparent overlap between the policy and regulatory function. The study concludes that the delays could be circumvented by separating the spectrum allocation and assignment into policy and regulatory functions respectively. Efficient spectrum management policy and regulation is important for the next stage of electronic communications revolution because of the advances in the technology such as broadband and agile radio.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Radio frequency spectrum; Policy; South Africa; Spectrum management